Effect of Solvents and Supporting Electrolytes on the Electrochemical Behaviour of Ferrocene/Ferricenium Redox System - A. Rostami, Abbas; Aram, Fatemeh (Asian Journal of Chemistry, 2010)
Cyclic voltammetric measurements were made using freshly polished glassy carbon to test ferrocene as a function of solvents and electrolyte composition. Apparent heterogeneous electron transfer rate constant, kåpp, of 0.0186, 0.0172, 0.0169 and 0.00487 cm/s were observed in 0.1 M NaClO4/CH3CN, 0.1 M NaClO4/DMF 0.1 M NaClO4/DMSO and 0.1 M (C2H5)4NClO4, respectively. The results of this work suggest that rate constant in several solvents revealed the expected trend of decreased rate in the lower dielectric constant. On the basis of the experimental results we concluded that increasing the ionic conductivity of solution decreases the magnitude of Ru (uncompensated cell resistance) and increases the electron transfer rate constant.